UJI KEAMANAN WEB PEMBELAJARAN DARING UNIVERSITAS PQR MENGGUNAKAN METODE OSSTMM (OPEN SOURCE SECURITY TESTING METHODOLOGY MANUAL) - Yohanne Mahrintan Siahaan (2021)
PQR University as an educational institution certainly provides various systems to support the learning process, one of which is the Online Learning web that stores various personal data of students, teachers, and related staff. The data stored on the Online Learning web is confidential, therefore system security is essential to ensure the confidentiality of the data of web users. This research was conducted to identify and provide recommendations on system vulnerabilities found through penetration tests against PQR University online learning sites. In this study, security testing was conducted using guidelines from the OSSTMM method. The research was conducted by testing two security channels, namely Data Network Security and Physical Security Channel. The actual security value obtained is 83.3464 for Data Network Security Channel and 85.1582 for Physical Security Channel. This suggests that system security on both channels still needs to be improved to avoid potentially damaging threats and disruptions to the asset.